DISTRIBUSI SPASIAL KESESUAIAN KUALITAS AIRTANAH UNTUK IRIGASI PADA TOPOGRAFI DATARAN DAN PERBUKITAN DI DAERAH TROPIS - Daffa Mughni Sopiandi; T N Adji; A I Mas’ud; B Azhar (Universitas Negeri Padang, 2023)
Groundwater is the primary irrigation water source when surface water does not meet its needs, especially during the dry season. Studying groundwater quality and its suitability for irrigation is crucial because it can have an impact on the quality of agricultural land, particularly the fertility of the soil and plants. This study aimed to distinguish the suitability of groundwater quality for irrigation purposes in plain and hilly topography. Groundwater samples were taken from 13 wells scattered throughout the study area, which includes plains and hills. Groundwater sample testing includes various parameters such as DHL, Cl-, HCO3-, Na+, B, K+, Mg2+, and Ca2+. Analysis of groundwater quality for irrigation uses several methods, namely salinity hazard, sodium hazard (SAR), RSC, ion toxicity, sodium percentage (%Na), magnesium hazard (MHR), Kelly's ratio, and permeability index. The analysis results show that most groundwater samples have excellent values for each analysis method. Spatially, groundwater samples from plains areas have better quality than those from wells in hilly areas. Even so, all groundwater in the plains and hills can still be used for irrigation purposes even though groundwater from wells on the hills has various potential hazards or adverse effects on soil and plants.